Preservation of dog semen at refrigeration temperature - KADIRVER, G; SREEKUMARAN, T (The Indian Journal of Animal Reproduction, 2023)
A total number of 36 semen ejaculates, six ejaculates from each dog was collected by digital manipulation from 6 Mongrel dogs at weekly interval. Immediately after semen collection physical and morphological characters were evaluated and go quality semen was extended in three extenders viz., egg yolk tris (EYT), egg yolk citrate glycine glucose (EYCGG) and goat milk (GM) extenders by split sample technique. Extended semen samples were preserved at refrigeration temperature and sperm motility, percentage of live sperm, abnormal spermatozoa and acrosomal integrity were evaluated at 24 hours interval for five days with the ultimate objective of recommending suitable extender for preservation of dog semen at refrigeration ,emperature. There w s significantly higher percentage of sperm motility and live sperm, lower perceotage of abnormal sperms and acrosomal damage m EYT and EYCGG than in GM. Eventhough, the values are not statistically significant among EYT and EYCGG. EYT was found to have higher percentage of sperm motility and live sperms, lower percentage of abnormal sperms and acrosomal damage when compared to EYCGG. Besides EYT was also found to have better clarity for microscopical examination ’hen compared t EYCGG. hence, it could be inferred that egg yolk tris is super.ior to egg yolk citrate glyc;ne glucose and goat milk for preservation of dog semen at 4°C.